‘Grande Herói da Banda’: The Political Uses of the Memory of Hoji ya Henda in Angola - Martins, Vasco (Journal of African history, 2022)
The article explores the political uses of the memory of the Popular Movement for the Liberation of Angola's (MPLA's) heroic combatant Hoji ya Henda from the independence of Angola in 1975 to recent times. Based on extensive archival work in Luanda, the article maps the historical periods and circumstances during which the ruling regime invoked Henda's memory, noting how changes in the political system directly affected how his memory permeated the public domain, oscillating between presence, silence, replacement, and resurgence. In doing so, the article explores a dilemma in the study of memory, opposing historical continuity and active construction in memory-making. It concludes that even when subjected to political manipulation for several decades, the original memorialisation of national heroes such as Hoji ya Henda, although subject to historical circumstance, always retains its original mnemonic signifier in society. This signals an important nuance in entrenched debates concerning the opposition between history and the political construction of memory.